Hospital Pharmacist Workforce in Eleven-Year 2006-2016 at Ministry of Health in Saudi Arabia - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objective: The workforce of hospital pharmacist is one the elements of pharmacy strategic plan in Saudi Arabia. The purpose of this study is to explore hospital pharmacist’s workforce in eleven years (2006-2016) at Ministry of Health in Saudi Arabia. Methods: It is a retrospective analysis of eleven years (2006-2016) of MOH hospital pharmacist workforce. All data were derived from Ministry of Health statistical yearbooks. It included pharmacist or clinical pharmacist’s workforces at MOH hospitals. The type of hospital included having bed capacity of 50-1500 beds with Adults public hospitals, pediatrics and maternity hospitals, Psychiatric hospitals, Diabetic centers, Cardiology centers, Oncology Centers, Renal Dialysis Centers, and Medical cities. All calculations were based on MOH workforce standards of hospitals. The calculations were per each region for a total of twenty-one regions; the hospital’s distribution numbers, the pharmacist distribution numbers, the ratio of pharmacist per hospital, the gender distribution of Pharmacist per region, the gender distribution of Saudi pharmacist per each region across Saudi Arabia. Result: The total numbers of hospitals were 276 hospitals, 2,325 primary care centers, and 20 administration regions. The total numbers of pharmacists were 3,520, distributed at hospital 2,760 (78.41 %), at primary care centers 430 (12.2 %) while administration regions 330 (9.37 %). The average numbers of hospitals were (251.36) with a range number of (220-274), and the total number was (274). The average numbers of hospital pharmacists were (1,617.55) with a range number of (636-2760), and the total number was (2760). The total gender distribution of all hospital pharmacists was male 1,077.4 (61.30%) and female 680.1 (38.70%). The total nationality distribution of all hospital pharmacists was Saudi 1342.03 (81.57%) and non-Saudi 303.26 (18.43 %(. Of Saudi primary care center pharmacist 861.05 (64.16%) was male and 480.98 (35.84%) was female. Conclusion: Number hospitals are increased over the past years. Despite the incremental number of hospital but the pharmacists over past years are same. Most of the hospital pharmacists were Saudi with more of half of staff were males. Targeting of the increasing number of Saudi hospital pharmacists through complete Saudisation standard is required.
Keywords: Hospital Pharmacist; Workforce; Manpower; Ministry of Health; Saudi Arabia